The world is coming to an end! COVID-19, depression, and anxiety among adolescents in Malawi - Mmanga, Chilungamo; Ndasauka, Yamikani; Kainja, Jimmy; Kondowe, Fiskani; Mchenga, Martina; Maliwichi, Limbika; Nyamali, Simunye (Frontiers in Psychiatry, 2023)
This paper assessed the effects of Covid-19 on adolescent mental health in Malawi. There is little research on adolescent mental health in Africa, Malawi in particular. The study shows a link between the pandemic and mental health. Some factors that may have contributed to this link include; Covid-19 preventive measures, media exposure and the increase in unemployment. The study used a mixed methods approach, quantitative and qualitative methods. It was conducted in Malawi's four districts (Blantyre, Mangochi, Lilongwe and Karonga). Overall, 22%, 21% and 23% of the respondents had depression, anxiety and post-traumatic stress disorder, respectively. The Chi-square test showed that significantly more adolescents with secondary education (28%) had anxiety than those with primary education (14%). Further, regression analysis revealed that adolescents with anxiety were 18 [95%CI: 9.34, 35.8] times more likely to have depression compared to those who did not have anxiety. The study found no significant differences in the proportions of adolescents with the three outcomes when comparing different groups within the explanatory variable. The ratio of female and male adolescents with depression and anxiety was the same. The adolescents expressed that Covid-19 affected their social, academic, and financial status. These effects had a significant bearing on their mental health in that they led to depression, anxiety, fear of the unknown, and stress. During the Covid-19 pandemic, adolescents' mental health diminished and posed a considerable risk to productivity of adolescents. As a result, adolescents may not fully realise their potential, form and maintain good relationships, contribute to their community and become resilient. These effects have devastating consequences for this young generation without proper coping strategies.